Codesigned recommendations for increasing engagement in structured physical activity for people with serious mental health problems in Australia. (26th July 2018) - Wheeler, Amanda J.; Roennfeldt, Helena; Slattery, Maddy; Krinks, Rachael; Stewart, Victoria
Abstract: People with mental health problems are at higher risk of physical health comorbidities and early mortality. A key risk factor for poor health outcomes is a lack of regular physical activity. Mental health services have typically responded by focusing on screening and promoting lifestyle programmes within secondary care mental health settings. The aim of this study was to better understand the barriers and enablers for Australian mental health consumers to participate in physical activity or exercise programmes from the perspectives of consumers and exercise practitioners. Interviews with 15 consumers experiencing serious mental health problems and five exercise practitioners were undertaken, followed by two focus groups (involving eight consumers and two exercise practitioners) to gain consensus on themes from the interviews, and codesign a set of recommendations for services to support and increase the engagement of mental health consumers in regular community‐based exercise. Barriers that impacted on engagement in physical activity included: lack of social support, insufficient knowledge and information, difficulties with work/life balance, impact of physical and mental health issues, fear and lack of confidence, and financial cost. Enablers or motivators assisting engagement in community‐based physical activity programmes included: social support, access to person‐centred individualised exercise options, connection and a sense of belonging, and access to information and education. Recommendations and a checklist were developed to assist services to increase the involvement of mental health consumers in community‐based exercise and to ensure that exercise practitioners and their employing organisations are adequately equipped to work with this population.